Starch of Curcuma angustifolia Roxb. in Comparison with other Starches of Forest Origin - Rani, Abha; Chawhaan, Pravin H. (Indian Forester, 2012)
Curcuma angustifolia Roxb. starch was isolated from the rhizomes and got purified. In C. angustifolia starch absolute density 1.45, fat/lipid content 1.23%, total ash 1.28%, acid insoluble ash 0.31%, sulphated ash 0.99%, water binding capacity 89.89%, gelatinization temperature ranged 75°C to 85°C and Barbender viscosity 4968 cps were recorded. The solubility of starch ranging from 1.28 to 46.68 and swelling power 2.58 to 49.05 from serially heating at 50°C to 95°C were obtained. The granule shape was rounded, oval to elliptical spherical and elongated from 3.32μto 32.55μ in length and 2.29μ to 23.76μ in width.